How was the SME’s Performance in Oman during Covid-19? - Al Taha, Atallah Firas (International Journal of Economics and Financial Issues, 2024)
The paper examines the performance and the challenges faced by SMEs in Oman during Covid-19. The data was collected through primary and secondary sources. A questionnaire of 100 respondents was used. Descriptive analysis and chi-squared test have been employed in the data analysis. The main findings of the study showed despite the adverse effect of the pandame, the SMEs in Oman have performed well and indicated a resilient and adaptable strategy to cope wth the virus. The reason for this could be attributed to their ability to quickly transition to remote work and online operations. During such a challenging period, some businesses managed to thrive due to their ability to identify opportunities and leverage them. Moreover, the study revealed that financial stability and preparedness are key to navigating the pandemic's uncertainties, as businesses focus on risk management, budget planning, and saving money. In response to unexpected disruptions, businesses have become more cautious and strategic in their financial decisions. SME resilience against future crises is enhanced as a result of SMEs adopting more prudent financial practices. The key challenges faced by SMEs during Covid-19 included delivery delays, reduced income for consumers, and regulation changes. The SMEs in Oman devised severalrisk management strategies, such as maintaining backup plans and setting aside funds, reflect a forward-thinking approach. The findings indicate that businesses in Oman are actively seeking ways to minimize disruptions to their operations and mitigate potential risks. Long-term resilience can be built by such strategic thinking.